Loss of Vacuolar H(+)-ATPase (V-ATPase) Activity in Yeast Generates an Iron Deprivation Signal That Is Moderated by Induction of the Peroxiredoxin TSA2 - Diab, Heba I. (American Society for Biochemistry and Molecular Biology, 2013)

(untitled)
Vacuolar H(+)-ATPases (V-ATPases) acidify intracellular organelles and help to regulate overall cellular pH. Yeast vma mutants lack V-ATPase activity and allow exploration of connections between cellular pH, iron, and redox homeostasis common to all eukaryotes. A previous microarray study in a vma mutant demonstrated up-regulation of multiple iron uptake genes under control of Aft1p (the iron regulon) and only one antioxidant gene, the peroxiredoxin TSA2 (Milgrom, E., Diab, H., Middleton, F., and Kane, P. M. (2007) Loss of vacuolar proton-translocating ATPase activity in yeast results in chronic oxidative stress. J. Biol. Chem. 282, 7125–7136). Fluorescent biosensors placing GFP under transcriptional control of either an Aft1-dependent promoter (P(FIT2)-GFP) or the TSA2 promoter (P(TSA2)-GFP) were constructed to monitor transcriptional signaling. Both biosensors were up-regulated in the vma2Δ mutant, and acute V-ATPase inhibition with concanamycin A induced coordinate up-regulation from both promoters. P(TSA2)-GFP induction was Yap1p-dependent, indicating an oxidative stress signal. Total cell iron measurements indicate that the vma2Δ mutant is iron-replete, despite up-regulation of the iron regulon. Acetic acid up-regulated P(FIT2)-GFP expression in wild-type cells, suggesting that loss of pH control contributes to an iron deficiency signal in the mutant. Iron supplementation significantly decreased P(FIT2)-GFP expression and, surprisingly, restored P(TSA2)-GFP to wild-type levels. A tsa2Δ mutation induced both nuclear localization of Aft1p and P(FIT2)-GFP expression. The data suggest a novel function for Tsa2p as a negative regulator of Aft1p-driven transcription, which is induced in V-ATPase mutants to limit transcription of the iron regulon. This represents a new mechanism bridging the antioxidant and iron-regulatory pathways that is intimately linked to pH homeostasis.